An investigation into the decametric radio emission by the planet Jupiter - Gruber, Georg M (Rhodes University, Faculty of Science, Department of Physics, 1967)
From introduction: Jupiter is the largest planet in the solar system. Its distance from the Sun is five times that of the Earth and its mass is nearly two and a half times that of all the other planets added together. Jupiter turns about its own axis rather rapidly, once in just under ten hours, and it completes one revolution about the Sun in just under twelve years. Thus Earth has to pass almost directly between the Sun and Jupiter once every thirteen months. When this happens Jupiter is said to be in "opposition", as its position is then opposite to that of the Sun, when viewed from Earth. Around this time the planet will be most favourably placed for observations, as it is at its closest to Earth and up in the sky for a large part of the night. During the day observations on radio frequencies are more difficult, as the Sun is a source of great interference. Besides being an emitter of thermal electromagnetic radiation, as one would expect, Jupiter also emits two kinds of non-thermal radiation, one in the decimetre wavelength range and the other in the decametre wavelength range. A large number of scientists have worked on the problems of decimetre and decametre radiation. This thesis deals with some aspects of decametre radiation.
Keywords: Jupiter (Planet); Radio astronomy; Radio sources (Astronomy)